PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 016 SEKELADI KECAMATAN TANAH PUTIH KAB. ROKAN HILIR - Semiyani Semiyani; Munjiatun Munjiatun; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract, The problem this research is the students achievement of social studies of state SDN 016 Sekeladi fourth graders still low with an average value of 60 and minimum completeness criteria (KKM) sains studies is 70. Between students, amounting to 18 people only 33,33%, this research is Classroom Action Research (CAR), which aims to improve the student achievement of sains studies class III at of state SDN 016 Sekeladi with implementation incuiri. Formulation of the problem : is the implementation incuirios social students can improve students achievement of social studies at of state SDN 016 Sekeladi. The research was conducted on Maret 03, 2015 to April 07, 2014 by 2 cycles. Subjects were students of of state SDN 016 Sekeladi, totaling 18 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets an students achievement. This thesis presents the results obtained each day before the action an improve in base score cycle with the average being 60. In the first cycle improve an average of 70 and an improve in the second with an average of 71,39. Activities of the teacher in the learning process in cycle of 66,66%, with increase big as 76,16% and the second meeting improve 87,50% and the second meeting improve 100%. Results of data analysis of students activities in the fisrt cycle with the fisrt meeting of an average of 54,20% and a second meeting improve to 70,80% and a second meeting improve to 91,70% at the first meeting of the second cycle with an average of 85,80%. However students achievement also increased the basic score of daily examonatoion as 66,67% which 12 students passed and 8 students failed. The ending of daily examonatoion as 72,22% which 13 students passed and 5 students failed. The Impemeltation Of Cooperative Learning Make A Match type, Resuts in the class III of state SDN 016 Sekeladi that the implementation of incuiri of social students can improve student achievement of sosial studies at fourth graders of state SDN 016 Siekeladi.Key Words : Model cooferative Learning Make A Match of social students, fourth graders students Achievement